2017
DOI: 10.1123/iscj.2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Coaching Workshop: Applying a Person-Centred Approach to Coach Development Programs

Abstract: It is well established that coach learning and athlete outcomes can be enhanced through participation in Coach Development Programs (CDPs). Researchers advocate that the quality of CDPs can be improved by: (a) placing a greater emphasis on facilitating coaches’ interpersonal behaviours (Lefebvre, Evans, et al., 2016), (b) using appropriate and systematic evaluation frameworks to guide the evaluation of interpersonally-focused CDPs (Evans et al., 2015), and (c) incorporating behaviour change theories into the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 41 publications
2
42
0
4
Order By: Relevance
“…Previous literature supports this finding that transformational leadership promotes motivation in employees and develops positive psychological states such as meaningfulness of work, experienced responsibility for the outcomes and knowledge of work results. It indicates that transformational leadership directly exerts its influence by helping employees or followers to think more positively about themselves and their tasks, by enhancing the quality of their relationships, and by creating environments that are fair, respectful, and supportive [86] and all of these factors contribute positively toward employee's self motivation toward his/ her work (i.e., intrinsic motivation). The positive elements of transformational leadership bring out positive psychological states by escalating intrinsic motivation among employees.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Previous literature supports this finding that transformational leadership promotes motivation in employees and develops positive psychological states such as meaningfulness of work, experienced responsibility for the outcomes and knowledge of work results. It indicates that transformational leadership directly exerts its influence by helping employees or followers to think more positively about themselves and their tasks, by enhancing the quality of their relationships, and by creating environments that are fair, respectful, and supportive [86] and all of these factors contribute positively toward employee's self motivation toward his/ her work (i.e., intrinsic motivation). The positive elements of transformational leadership bring out positive psychological states by escalating intrinsic motivation among employees.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Several reviews have concluded there is a need for CDPs that are grounded in behavioral change theories (Allan et al, 2017;Evans et al, 2015;Lefebvre et al, 2016). Turnnidge and Côté (2017) suggest integrating interpersonal theories into coach education both to explore the interpersonal dimension of coach-athlete interactions and to design effective, interpersonally-focused CDPs. Self-determination theory (Ryan & Deci, 2017) is one such theory.…”
mentioning
confidence: 99%
“…These behaviors resonate with previous leadership theories. For example, outlining an athlete's potential and providing encouragement has links with the inspirational motivation dimension of TFL . In addition, making sacrifices for athletes appears to relate to self‐sacrificial leadership …”
Section: Discussionmentioning
confidence: 99%
“…For example, inspirational motivation would satisfy the transcendence characteristic of inspiration because leaders articulating an exciting vision of the future may make followers aware of better possibilities. Research in sport by Turnnidge and Côté has further highlighted how coaches can show TFL behaviors to inspire followers (eg, by discussing goals and expectations). However, while TFL provides useful suggestions into how inspiration can be evoked by leaders, there are several theoretical issues with TFL that have been identified in contemporary reviews within organizational and sport literature.…”
Section: Introductionmentioning
confidence: 99%